Pembuatan Aplikasi Sistem Informasi Akuntansi pada CV. X di Surabaya - Sumargo, Jennifer Giovanni; Setiawan, Alexander; Rostianingsih, Silvia (Jurnal Infra, 2016)
CV. X is a company in Surabaya which distributes stationeries and plastic roofing sheets. In doing their business process, all sales and consignment transactions is recorded in a software, but this software is not compatible for CV. X. The problems encountered are non-flexible consignment report, VAT not showing, and price differentiation between transfer-in and transfer-out. Based on this background, a structural accounting information system is designed to overcome the problems.The results obtained from the system are master recording for suppliers, customers, salespersons, and goods data. Transactions include purchases, purchase returns, sales, sales returns, and consignment. All transactions have been integrated with inventory stock card and the journal. This application also generates financial statement such as income statement, ownerâs equity statement, and balance sheet. The system was build using PHP as the programming language and MySQL database.Overall this application meets the company requirements. This is proven by 100% user is quite satisfied with the completeness of information and 67% user is satisfied with the reports.